Two Novel Mutations in ABHD12: Expansion of the Mutation Spectrum in PHARC and Assessment of Their Functional Effects. Issue 12 (2nd October 2013) - Chen, Dong‐Hui; Naydenov, Alipi; Blankman, Jacqueline L.; Mefford, Heather C.; Davis, Marie; Sul, Youngmee; Barloon, A. Samuel; Bonkowski, Emily; Wolff, John; Matsushita, Mark; Smith, Corrine; Cravatt, Benjamin F.; et al.
<x xml:space="preserve">Abstract</x> We identified two novel mutations in ABHD12 in a woman with PHARC, a heterozygous p.Lys377* mutation and a 59‐kb deletion that encompasses exon 1 of ABHD12, exons 1‐4 of GINS1, and the promoters of both genes. In this first functional study of the effect of ABHD12 mutations, we demonstrated a 50% decrease in ABHD12 RNA expression and absence of ABHD12 hydrolase activity. Haploinsufficiency for GINS may play a role in the short stature of the patient and her mother. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>